Private Security and Municipal Policing in Academic Education – An International Overview - Kovács, Éva; Christián, László (Magyar Rendészet, 2019)
The objective of the research group entitled The role of private security and local governmental law enforcement in 21st century law enforcement is to comprehensively examine the field of private and municipal policing regarding its domestic situation with an international outlook. Analysing this issue, the question of how, in what detail and at which training levels the education of these two fields are conducted bears utmost importance in countries under our scrutiny, along with regulatory, organisational and operational issues. The selection of the countries was done subjectively, in line with the work of our research group.